Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/adpr.202200040
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Broadband Photoresponse Electron‐Emission Nanostructure: Metasurface‐Extended Spectrum‐Selecting and Plasmon‐Enhanced Emitting

Abstract: Exploring novel nanotechnology schemes for tunable broadband vacuum photodetection devices is of great significance. Herein, a strategy to combine a field‐emission cold cathode with plasmonic nanostructures to form a plasmon‐enhanced field‐emission metasurface array is proposed. Mo nanostructures with excellent emission properties act as field‐emission cold cathode materials. Au nanospheres are applied to enhance the photocurrent of Mo nanopyramid emitters and to generate tunable resonance responses by plasmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
(57 reference statements)
0
3
0
Order By: Relevance
“…In many studies, the researchers found that the photogenerated electric field can be ignored even if the irradiation power of incident light is as high as several 10 4 W cm −2 because the photoelectric field is far lower than the applied field. [55] The finite-difference time-domain (FDTD) simulation is carried out to further analyze the effect of the photogenerated electric field on the FE process of ML WS 2 with microtips, as seen in Figure S4, Supporting Information. Combined with the FDTD simulation and recent research results, the effect of the photogenerated field on the FE process of ML WS 2 with microtips can be ignored in our measurements.…”
Section: Resultsmentioning
confidence: 99%
“…In many studies, the researchers found that the photogenerated electric field can be ignored even if the irradiation power of incident light is as high as several 10 4 W cm −2 because the photoelectric field is far lower than the applied field. [55] The finite-difference time-domain (FDTD) simulation is carried out to further analyze the effect of the photogenerated electric field on the FE process of ML WS 2 with microtips, as seen in Figure S4, Supporting Information. Combined with the FDTD simulation and recent research results, the effect of the photogenerated field on the FE process of ML WS 2 with microtips can be ignored in our measurements.…”
Section: Resultsmentioning
confidence: 99%
“…Beyond the typical precious metals, such as Au, [115][116][117] Ag, [118] Pt, [119] Ir, [120] and Pd, [121] there also exist several non-precious metals manifesting pronounced plasmonic effects, including Al, [122,123] Cu, [124][125][126] In, [127] Mo, [128] Sn, [129] Mg, [130] Sb, [131] Cu-Ni alloy, [132] Ga-In alloy, [133] etc. With the advantage of much lower cost, these materials have provided promising alternatives for the optical engineering research of next-generation optoelectronic devices.…”
Section: Non-noble Metal Optical Antenna Promoted 2dlm Photodetectorsmentioning
confidence: 99%
“…Second, electrons pumped into the vacuum may be confined to a nano or even atomic scale by the nano-cold-cathode materials employed. Third, the electron emission yield and quantum efficiency are believed to be significantly improved, with the assistance of applied electrostatic field 30,31 and plasmon-enhanced nearfield 32,33 that may exist, and simultaneously the driving power consumption for the cathode and device are greatly reduced. These advantages are particularly important for point electron sources, where the performance demand of electron beam from an individual emitter is extremely high, such as low energy spread, high brightness and low energy consumption.…”
Section: Introductionmentioning
confidence: 99%